2015
DOI: 10.1002/path.4632
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐species models of human melanoma

Abstract: Although transformation of melanocytes to melanoma is rare, the rapid growth, systemic spread, as well as the chemoresistance of melanoma present significant challenges for patient care. Here we review animal models of melanoma, including murine, canine, equine, and zebrafish models, and detail the immense contribution these models have made to our knowledge of human melanoma development, and to melanocyte biology. We also highlight the opportunities for cross‐species comparative genomic studies of melanoma to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 138 publications
0
58
0
1
Order By: Relevance
“…This suggests the existence of a different biological pathway in the melanoma development at early ages not linked to coloration, distinct from the mostly benign condition in grey horses linked with the age and greying regulation (e.g. dermal melanomatosis) [17,22,23]. In fact, the interaction age/coat colour was not only significant in the S3 population for Melanoma.…”
Section: Discussionmentioning
confidence: 91%
“…This suggests the existence of a different biological pathway in the melanoma development at early ages not linked to coloration, distinct from the mostly benign condition in grey horses linked with the age and greying regulation (e.g. dermal melanomatosis) [17,22,23]. In fact, the interaction age/coat colour was not only significant in the S3 population for Melanoma.…”
Section: Discussionmentioning
confidence: 91%
“…To further investigate the influence of melanin on SWI, we performed a complementing in vitro experiment with a melanin-producing melanoma cell line. The SWI signal behavior of B16 melanoma cells, a common preclinical model of MM, 25 was compared with nonmelanotic U87 glioma cells, 26 which served as a negative control at 9.4 T and 3 T. Erythrocytes that are known to cause SWI blooming artifacts were used as a positive control. B16 melanoma cells, despite the high production of black melanin pigment, only showed a moderate signal drop in SWI compared with erythrocytes at 3 T (Fig.…”
Section: In Vitro Analysis Of the Melanin Susceptibility Effectmentioning
confidence: 99%
“…The highly aggressive biological behavior of hMMs (11) and the scarcity of available cases led to many attempts to establish a reliable animal model for the study of this life-threatening disease. Various in vivo models have been proposed for melanocytic derived-tumors through genetically engineered mice and zebrafish (12). Relevant limitations of these models are the lack of tumor population heterogeneity, combined with the longtime of tumor formation (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Various in vivo models have been proposed for melanocytic derived-tumors through genetically engineered mice and zebrafish (12). Relevant limitations of these models are the lack of tumor population heterogeneity, combined with the longtime of tumor formation (12,13). Altogether, these studies revealed the necessity of a spontaneous tumor model in non-engineered animals.…”
Section: Introductionmentioning
confidence: 99%